Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Karunia Ultima Kemasan Jatikalen Nganjuk - Rohman, Saiful Nur; Ambarwati, Diana; Saptaria, Lina (Populer: Jurnal Penelitian Mahasiswa, 2023)
The purpose of this research is to determine and explain the partial and simultaneous effects of workload and work environment on employee performance at PT. Karunia Ultima Kemasan. This study employs a quantitative approach and includes the entire population of employees at PT Karunia Ultima Kemasan in Jatikalen Nganjuk. A saturated sample was used, comprising 76 employees of PT Karunia Ultima Kemasan in Jatikalen Nganjuk, selected through the distribution of questionnaires directly to the respondents. The data analysis was conducted using multiple regression analysis. The results of the research indicate that workload and work environment have a positive and significant influence on employee performance.